La source principale du Quod Christus sit Deus attribué à Jean Chrysostome : la Démonstration évangélique d’Eusèbe de Césarée - Morlet, Sébastien (Revue d'études augustiniennes et patristiques, 2012)
Since N. G. McKendrick’s edition, critics have not paid much attention to the work entitled Quod Christus sit Deus, attributed to Chrysostomus. A precise analysis of its argumentation, notably its collection of testimonia, leads to the hypothesis that its main source is Eusebius’ Demonstratio euangelica. Besides, one wonders to what extent the Quod Christus sit Deus may be a witness of the last ten lost books of the Demonstratio.